Microstructure and Superconducting Properties of Rapid Heating, Quenching, and Transformation (RHQT) Powder‐in‐Tube Nb3Al Wires Doped with Sn Element. Issue 16 (8th July 2021) - Hu, Yuanbin; Ran, Mingming; Chen, Ming; Yu, Xuan; Liu, Lian; Chen, Yongliang; Zhang, Yong; Yu, Zhou; Zhao, Yong
Abstract : Properties of rapid heating, quenching, and transformation (RHQT)‐treated powder‐in‐tube (PIT) Nb3 Al1− x Sn x wires are studied herein. After the RHQ process, the body‐centered cubic (bcc) phase is formed in the Sn‐doped Nb3 Al wires. The transformed superconducting A15 phase shows a uniform microstructure and homogenous component distribution feature. With the increase of the Sn doping level, the critical transition temperature ( T c ), critical current density ( J c ), and irreversibility field ( B irr ) of the superconducting wires increase first and then reduce, achieving the highest T c value of 17.6 K and the smallest Δ T c of 0.6 K in the 4% Sn doped Nb3 Al wire. The 4% Sn addition helps to improve the layer J c of the sample to 2.1 × 10 5  A cm −2 at 8 K and 5 T, which is about 2.5 times that of the pure Nb3 Al sample. Furthermore, the Nb3 Al1− x Sn x ( x  = 0.04) wire gives the highest B irr value of 17.22, 13.23, and 9.11 T at 8, 10, and 12 K, respectively. The addition of Sn helps to achieve stoichiometric Nb3 Al A15 phase and formation of precipitations with the size of 10 nm, which might act as the flux‐pinning center. Abstract : Single‐A15‐phase Nb3 Al1− x Sn x ( x  = 0–0.1) superconducting wires that transform from the body‐centered cubic (bcc) phase are prepared by the rapid heating, quenching, and transformation (RHQT) method. The effect of Sn addition on the crystal structure, microstructure, and superconducting properties of Nb3 Al1− x Sn x wires is studied.